Kompensasi Berbasis Kinerja: Solusi pada Promosi dan Dinamika Kompetisi Internal Perusahaan - Ruslaini Ruslaini; Grace Yulianti; Sri Utami Nurhasanah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study examines the challenges in applying contract theory, particularly regarding firm performance-based pay as a solution to promotion risk in a competitive environment. Performance-based compensation aims to enhance employee motivation and reduce promotion uncertainty, but it can also lead to unhealthy competition and undermine team collaboration. This study suggests that a balanced incentive contract design, which combines financial and non-financial rewards, can optimize individual performance without sacrificing team harmony. While performance-based pay can offer short-term benefits, it is important for companies to consider its long-term impact on employee satisfaction and collaboration within the organization. This research provides theoretical and practical insights for firms in designing fair and effective promotion systems.